تأثير درجة الحرارة، pH، الإضاءة، والمستنبتات في نمو Colletotrichum gloeosporioides المسبب لمرض الأنثراكنوز في ثمار الحمضيات - حسن محمود; علّاف عصام; زيدان ليلى منيف (Latakia University Journal -Biological Sciences Series, 2013)
دُرس في المختبر تأثير درجات مختلفة من الحرارة، مستويات مختلفة من pH، فترات مختلفة من الإضاءة وأربعة مستنبتات غذائية هي (PDA، OMA، MEA،CzA) في نمو الفطر C.gloeosporioides المسبب لمرض الأنثراكنوز في ثمار الحمضيات، وأشارت النتائج إلى أنّ نمو الفطر كان أعظمياً في درجة الحرارة 30°م، و pH = (5.5، 6، (6.5، وأنّ الإضاءة غير ضرورية لنمو هذا الفطر . أعطى المستنبتان PDA، OMAمن بين المستنبتات المختبرة أقصى نمو للفطر C.gloeosporioides. Effect of different degrees of temperature, different levels of pH , different periods of light and four media (PDA, OMA, MEA, CzA) was studied in vitro against the growth of C. gloeosporioides causing anthracnose disease of citrus fruits. The results indicated that the growth of fungus was maximum at temperature 30°C and at pH = (5.5,6,6.5), and Light was unnecessary for the growth of C. gloeosporioides. Among the different media tested PDA and OMA supported the maximum growth of fungus.